Should the list of authorised trustee investments in the Irish Free State be extended? - Eason, Charles (Statistical and Social Inquiry Society of Ireland, 1932)
I recommend that to the list of authorised investments should be added some Free State Securities, some Securities in Northern Ireland and some in Foreign Countries and British Dominions. But before doing so I review the history of the law relating to Trustee securities in England?then state what the law now is in the Free State and draw attention to the English Trustee Act of 1925, and the report of the Trustee Securities Committee of 1928. I then give a sketch of the duties of the Public Trustee in the Irish Free State and of the Public Trustee in England. I then give suggestions for the extension of the list of authorised investments in the Irish Free State.
Read before the Society on Thursday, November 12th, 1931
Keywords: Trustee investments; National loans; Irish Free State; 314.15